Disaster Resilience Analysis in Vulnerable Groups Through Contingency Planning And Community-Based Emergency Services in the Martubung Region Medan City, North Sumatra Province, 2026 - Nurmalina Hutahaean; Merrygrace Simanjuntak; Putri Angelina Hutahaean; Srilina Br Pinem; Elvis Simanjuntak (Open Access Health Scientific Journal, 2026)
Background: Vulnerable groups are at high risk of being impacted by disasters and therefore require increased resilience through contingency planning and community-based emergency services. This study aimed to analyze changes in vulnerable groups' knowledge regarding disaster resilience before and after community-based contingency planning and emergency education interventions.Methods: This study used a quasi-experimental design with analytical research using a pretest–posttest design without a control group. The sample consisted of 32 vulnerable group respondents in the Martubung area. The instrument was a knowledge questionnaire. Data analysis was conducted descriptively and comparatively.Results: The research also showed that participants experienced an increase in knowledge during the post-test. The pre-test results showed that the majority of respondents had insufficient knowledge (87.5%). After the intervention, there was an increase in knowledge, with 46.9% of respondents categorized as good and sufficient, respectively.Conclusion: Community-based contingency planning and emergency services effectively increase the knowledge of vulnerable groups in disaster preparedness and resilience